PENGARUH EDUKASI PERSONAL HYGIENE PADA SAAT MENSTRUASI TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI DI PESANTREN AN-NUR TAHUN 2026 - Keysha Amelia; Silvia Mariana; Sunarti Lubis; Reni Hariyanti (Jurnal Kesehatan dan Pembangunan, 2026)
Issues regarding personal hygiene among adolescent girls include the use of unclean sanitary pads, the use of reused cloths dried in secluded areas away from sunlight, the use of non-absorbent underwear, and inadequate genital hygiene. This study aimed to explore the effect of menstrual hygiene education on the knowledge and attitudes of adolescent girls at the An-Nur Islamic Boarding School in 2026. A quasi-experimental study design with a one-group pretest-posttest approach was employed. The study was conducted at the An-Nur Islamic Boarding School in January 2026, involving a total of 44 respondents selected through total sampling. Data analysis was performed using the Paired Sample T-Test. The results showed significant changes in the knowledge and attitudes of the adolescent girls before and after the intervention, with p-values ??of 0.001 (p < 0.005) for knowledge and 0.001 (p < 0.005) for attitudes. The study concludes that the menstrual hygiene education provided had a significant impact on the knowledge and attitudes of the adolescent girls at the An-Nur Islamic Boarding School.